2021
DOI: 10.47108/jidhealth.vol4.issspecial1.97
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice towards COVID-19 among Libyan people- a web-based cross-sectional study

Abstract: Background: Successful plans in disaster and epidemics management depend on the feedback response and the assessment of knowledge, attitudes, and practices among the target population. This study aims to assess the knowledge, attitude, and practice towards COVID-19 among Libyan people.  Methods: A cross-sectional web-based survey designed to assess the knowledge, attitude, and practice towards COVID-19 among the Libyan people from 13-20 October 2020. A self-administered questionnaire was recruited to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…However, there was no significant difference between the genders in their attitudes toward COVID-19. This was in line with some past research studies [ 35 , 36 , 47 ] but in contrast to other studies [ 19 , 33 , 37 , 62 ]. Regarding practices, the findings revealed that good practices were associated with female respondents.…”
Section: Discussionsupporting
confidence: 93%
“…However, there was no significant difference between the genders in their attitudes toward COVID-19. This was in line with some past research studies [ 35 , 36 , 47 ] but in contrast to other studies [ 19 , 33 , 37 , 62 ]. Regarding practices, the findings revealed that good practices were associated with female respondents.…”
Section: Discussionsupporting
confidence: 93%
“…In the linear regression analysis, women showed a more positive attitude (P=0.022) toward COVID-19 than men. Several previous studies [14][15][16][27][28][29][30][31] reported higher morbidity and mortality rates among men than women. Peckham et al [28] found that the likelihood of needing an intensive therapy unit is approximately three times higher for men than for women.…”
Section: Discussionmentioning
confidence: 93%
“…Data was collected using a self-administered survey from October to December 2020 in Anbar province, Western Iraq. The current study is part of a larger research initiative [14][15][16], in which we recruited a web-based survey to explore the knowledge, attitude, and practice among the general population.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence rate of tobacco smoking is higher among men than women, which increases their risk of lung disease [10], while women have a high level of immunity due to an increase in the X chromosome [11]. Previous studies found that women are more committed to protection standards from the coronavirus than men [12,13,14]. Furthermore, men are more commonly employed in jobs outside the home and most likely subjected to less social distancing rules.…”
Section: Discussionmentioning
confidence: 99%